The rise and decline of job insecurity - Francis Green (University of Kent, Department of Economics, 2003)
Job security is an important aspect of work quality. Accumulating evidence shows that insecurity has deleterious impacts on individuals and households, and in the mid-1990s, job insecurity became a public and political issue. This paper critically examines the concept and measurement of job insecurity and examines trends based on representative survey data in a number of industrialised countries. There is some evidence that insecurity increased in the 1970s and 1980s. However, perceived rising insecurity during the 1990s was a middle-class phenomenon based in part on the experience of professional workers and on the finance industry. In recent years, most occupation groups in Britain have experienced declining insecurity, reflecting a return to historically low levels of unemployment. Insecure workers are concentrated in jobs with temporary contracts and short job tenures, and in the private sector. Plant and Machine Operators remain especially insecure. Workers in foreign-owned firms are experiencing greater insecurity in recent years, and this link is associated with competition from low-wage economies.
Keywords: J2; J6; 330; Job security; job insecurity; unemployment; Arbeitsplatzsicherung; Ungeschützte Beschäftigung; Vergleich; USA; Großbritannien; Deutschland